Lulu's Secrets to Looking Good - Lulu (London Harper Collins, 2010)
Lulu is the ultimate beauty icon for women - small in stature, but big in personality and attitude, she's renowned for looking fantastic for her age. How does she do it? For the first time ever, Lulu finally reveals her secrets for looking youthful, glamorous and polished, whatever the occasion. With her honest, down-to-earth style, she opens up about the day-to-day fashion and beauty tricks she's picked up over the years to ensure she always looks and feels her best.
Include Color Illustration,Index and Directory
Keywords: Women's clothing -- Beauty, Personal